Qualidade fisiológica de sementes de girassol de diferentes tamanhos - (:unkn) unknown (Universidade Federal do Pampa, 2025)
Seed physiological quality during storage can be influenced by physical traits such as size. This study evaluated the physiological behavior of sunflower seeds classified into three sizes (2.36 mm, 4.75 mm, and 4.8 mm) over 150 days of storage under semi-hermetic conditions. Variables such as germination, vigor, seedling length, emergence speed index (ESI), sphericity, and the incidence of abnormal seedlings and dead seeds were analyzed. The experiment followed a completely randomized design in a 3x3 factorial scheme with four replications. Data were subjected to analysis of variance, and significant means were compared using Tukey’s test at 5% probability, with the Sisvar software. The results showed a significant influence of seed size on the maintenance of physiological quality during storage. Smaller seeds (2.36 mm) exhibited greater stability over time, while larger seeds (4.75 mm) were more prone to deterioration. Seeds of 4.8 mm showed intermediate performance. Thus, smaller seeds are recommended for long-term storage due to better preservation of viability and physiological performance.
Keywords: Engenharia agrícola; Girassóis; Sementes - Armazenamento; Sementes - Fisiologia; Sementes - Qualidade; Agricultural engineering; Sunflowers; Seeds - Storage; Seeds - Physiology; Seeds - Quality; CIENCIAS AGRARIAS